The safety and efficacy of hypovolemic phlebotomy on blood loss and transfusion in liver surgery: a systematic review and meta-analysis. Issue 3 (March 2020) - Park, Lily; Gilbert, Richard; Baker, Laura; Shorr, Risa; Workneh, Aklile; Turcotte, Simon; Bertens, Kimberley A.; Abou-Khalil, Jad; Balaa, Fady K.; Martel, Guillaume
Abstract: Background: Hypovolemic phlebotomy (HP) is a novel intervention that involves intraoperative removal of whole blood (7–10 mL/kg) without volume replacement. The subsequent central venous pressure (CVP) reduction is hypothesized to decrease blood loss and the need for blood transfusion. The objective was to conduct a systematic assessment of the safety and efficacy of HP on blood loss and transfusion in the liver surgery literature. Methods: MEDLINE, EMBASE, and Cochrane Library databases were searched. Outcomes of interest included blood loss, allogenic red blood cell transfusion, postoperative adverse events, and CVP change. A qualitative synthesis and meta-analysis were performed as appropriate. Results: Four cohort studies, one case series, and three randomized controlled trials involving 2255 patients were included. Meta-analysis of studies involving liver resections for any indication (n = 6) found no difference in transfusion (OR 0.38, p = 0.12) or incidence of adverse events with HP compared to non-use. Pooling of studies involving liver resections for an underlying pathology (n = 4) revealed HP was associated with significant reduction in transfusion (OR 0.25, p = 0.03) but no differences in blood loss (−173 mL, p = 0.17). Conclusion: This review suggests HP is safe and associated with decreased transfusion in patients undergoing liver surgery. It supports further investigation.